Plasma Apolipoprotein-M (ApoM) Response to a Circuit Resistance Training Program - Abbass Ghanbari-Niaki (The Society of Aging and Physical Activity (SAPA), 2013)
Apolipoprotein M (Apo-M) is a human novel protein of apolipoprotein classes and highly expressed in liver and kidney tissues. ApoM is mainly associated with high-density lipoprotein (HDL), and act as a chaperone for sphingosine-1-phosphate (S1P), promotes mobilization of cellular cholesterol, formation of larger-size of pre β-HDL, and a new biomarker in sepsis. The level of apoM in plasma/serum is affected by several factors such as pregnancy, hyperglycemia, plasma leptin concentration, obesity, diabetes, insulin concentration and physical exercise. It has been shown that the level of plasma ApoM was significantly lower in strenuous exercise group when compared with the non-exercise group. In the present study a reduction was observed after the 4 weeks of circuit resistance training program. This reduction might be due to a decrease in ApoM expression in liver and kidney or an increase in ApoM clearance, degradation and excretion in urine.